Echocardiographic Changes in Patients with End-Stage Renal Disease at Initiation of Dialysis - Shabana Nazneen; Muzamil Latief; Manjusha Yadla (Journal of Renal and Hepatic Disorders)
Introduction: Echocardiography is a simple and established method of evaluating cardiac functions, assessing left ventricle geometry, and systolic and diastolic functions. Patients with chronic kidney disease have a tremendous burden of cardiovascular disease (CVD), and patients with end-stage renal disease (ESRD) are at a greater risk of CVD and deaths. Materials and Methods: In this study, 245 incident dialysis patients were included, and none of the patient was on erythropoietin. All the patients were aged >18 years. Patients with ESRD, already on maintenance dialysis, were not included in this study. Patient’s data such as demographic details, comorbidities, laboratory values, echocardiographic changes, management, and outcome were recorded. Results: Out of 245 patients, 165 (67.3%) were males and 80 (32.6%) females. The mean age of the patients was 49.7 years. Left ventricular hypertrophy (LVH) was observed in 188 (76.7%), mild left ventricular dysfunction (LVD) in 25.7%, moderate LVD in 23.67%, severe LVD in 8.5%, global hypokinesia in 33.8%, valvular heart disease in 26.5%, regional wall motion abnormality in 4.4%, and pericardial effusion in 1.6% patients. Echocardiographic changes, such as LVD, LVH, and global hypokinesia, were observed in greater number in hypertensive group com-pared to normotensive group (P < 0.05). On regression analysis adjusted for age and gender, we found that hypertension and anemia (<10 g/dL) were associated with LVH. Further, hypertension and anemia (Hb < 10 g/dL) were associated with LVD. Similarly, anemia (Hb < 10 g/dL) was associated with global hypokinesia and valvular heart disease. LVD was associated with death in our study. Conclusion: Echocardiography is a noninvasive diagnostic test which detects early changes in cardiac parameters. All ESRD patients with hypertension and anemia at the time of initiation of renal replacement therapy must undergo echocardiography screening.